The atomic scale structure of saccharose-based carbons. Issue 20 (13th July 2017) - Woźnica, N.; Hawełek, ᴌ.; Duber, S.; Fischer, H. E.; Honkimäki, V.; Pawlyta, M.; Bulou, A.; Burian, A.
Abstract: Activated carbons (ACs) have a wide range of applications, in which the largely expanded specific surface plays a major role. The question of their structure came back to the limelight with the discovery of nanotubes fullerenes, which suggested that curved surfaces may be present in their structure and which incorporates well into the ideas of ACs porous structure. The source of those curved surfaces is atomic defects present inside the in-plane graphitic honeycomb lattice. Such defects have a crucial influence on the macroscopic morphology as well as physical properties of the material. The activated carbon (AC) in this work was derived from carbonised saccharose by activation with NaOH. Both materials – before and after activation were investigated. The main methods used in this study are wide angle neutron scattering and wide angle X-ray scattering combined with computer simulations. Confirmation of the proposed structures was sought with high-resolution transmission electron microscopy and Raman scattering. In this case, the use of classical crystallography to interpret experimental data was impossible due to the lack of periodic three-dimensional symmetry. Due to this fact, the data was analysed both in real and reciprocal space in the form of a pair correlation function and a structure factor. The experimental data were compared with calculated atomistic models. As a validation, the discrepancy factor between the theoretically and experimentally obtained functions was used. The presented innovative approach can be applied to different carbon materials with varying degrees of disorder.